AR 2017
DOI: 10.21873/anticanres.11960
|View full text |Cite
|
Sign up to set email alerts
|

Topical Management of Acute Radiation Dermatitis in Breast Cancer Patients: A Systematic Review and Meta-Analysis

Abstract: (OR: 0.29; p<0.0001) and reducing the mean RD score p<0.00001 Radiation induces damage to the skin, activating inflammatory pathways and causing cytokines overproduction (1, 2). Radiation dermatitis is a common acute side-effect that occurs within hours to weeks after the start of radiotherapy (3, 4) and affects more than 87% of patients (2, 5). Radiation dermatitis can limit the therapeutic dose delivered to patients and can, sometimes, lead to a break in treatment, thus potentially compromising local contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 43 publications
0
37
1
9
Order By: Relevance
“…To our knowledge, this is the first randomized trial demonstrating the superiority of a film-forming silicone gel in reducing in vivo 34: 413-422 (2020) RD during breast RT based on objectively measured physiological skin parameters. Despite decades of investigations, no clear evidence of the superiority of any single topical agent in the prevention of RD has emerged (10,(17)(18)(19)(20)(21)(22)24). Although steroids have been proven to be potent topical agents in reducing RD (31,32), the use of steroids requires a doctor's prescription and is not free of criticism.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first randomized trial demonstrating the superiority of a film-forming silicone gel in reducing in vivo 34: 413-422 (2020) RD during breast RT based on objectively measured physiological skin parameters. Despite decades of investigations, no clear evidence of the superiority of any single topical agent in the prevention of RD has emerged (10,(17)(18)(19)(20)(21)(22)24). Although steroids have been proven to be potent topical agents in reducing RD (31,32), the use of steroids requires a doctor's prescription and is not free of criticism.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a variety of interventions are used for topical therapy of ARD, however, randomized controlled trials (RCTs) have not yet consistently indicated the superiority of any single agent ( 15 ). In a pooled analysis and systematic review, the prophylactic application of topical corticosteroid in breast cancer patients undergoing radiotherapy appears to significantly reduce the incidence of ARD, specifically moist desquamation, compared with other treatments ( 16 , 17 ). However, the use of topical steroids may result in thinning of the SC, which leads to the transepidermal water loss (TEWL) and skin irritation ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de alguns estudos randomizados terem sido ou estarem sendo conduzidos para avaliar as estratégias de prevenção e de tratamento de radiodermatites, muitas intervenções, comumente utilizadas na prática clínica, são baseadas na tradição ou na opinião dos profissionais e em experiências institucionais, além de não serem pesquisadas exaustivamente (Feight et al, 2011;Fernandez-Castro, Martin-Gil, 2015;Glover, Harmer, 2014;Kole, Kole, Moran, 2017;Kodiyan, Amber, 2015;Singh et al, 2016). Na literatura específica sobre o tema, pode-se constatar a falta de evidências acerca das recomendações sobre intervenções ou produtos (de uso oral ou tópico), alguns dos quais reportados por enfermeiros e médicos (Chan, Larsen, Chan, 2012;Chan et al, 2014;Feight et al, 2011;Fernandez-Castro, Martin-Gil, 2015;Glover, Harmer, 2014;Haruna, Lipsett, Marignol, 2017;Kodiyan, Amber, 2015;Kole, Kole, Moran, 2017;McQuestion, 2011;Meghrajani et al, 2013;Salvo et al, 2010;Singh et al, 2016;Waghmare, 2013).…”
Section: Introductionunclassified
“…Dentre os produtos tópicos identificados na literatura, incluem-se loções, cremes, pomadas e coberturas especiais (Bolderston et al, 2006;Chan, Larsen, Chan, 2012;Haruna, Lipsett, Marignol, 2017;McQuestion, 2011;Meghrajani et al, 2013;Salvo et al, 2010). Além desses, estratégias como a fotobiomodulação com laserterapia de baixa intensidade (Censabella et al, 2016;Costa et al, 2014;Robijns et al, 2018;Seité, Bensadoun, Mazer, 2017) e o uso tópico de vasoconstritores adrenérgicos (Cleary et al, 2017;Fahl, 2016) também têm sido reportadas.…”
Section: Introductionunclassified
See 1 more Smart Citation